PENCIPTAAN LAGU ANAK UNTUK MITIGASI BENCANA GEMPA DAN TSUNAMI DI DAERAH PESISIR PANTAI KOTA PARIAMAN DAN KABUPATEN PADANGPARIAMAN SUMATERA BARAT - Sastra Munafri; Bambang Wijaksana (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
The objective of this research was to compose the child song as the mitigation of earthquake and tsunami disaster to build the character and mental to elementary School student in the coastal city of Pariaman and Padang Pariaman district, West Sumatra Province. This research was conducted in eight (8) Elementary School (SD) in the Pariaman city and Padang Pariaman district. The research method was a survey method with purposive sampling the elementary school is located ± 1 km from the coast. The research was done to collect the data base and characteristics of sample, compose song lyrics, compossing music, the song arrangements and recording process. The data were analyzed descriptively, questionnaires were used to test the understanding of the child at the beginning of the study. The results showed that a total 477 elementary students, 256 men and 191 women, in general, the elementary school students are afraid of the earthquake and tsunami and the action was taken screaming and istigfar. Only 41.39% of respondents who had received education about disaster mitigation efforts of NGOs and BPBD. The kids love the songs and music of 90%, but their knowledge of local music is very low. Lyrics composed by the popular pop style. Composition of song lyrics consisting of five verses of four lines (sentences). The first about geografis condition, the second educating the earthquake and tsunami, the third self-control, the fourth contains the actions to be taken and the fifth verse is the climax, action and pray.